DISEMINASI TEKNOLOGI PENGEMBANGAN PUPUK ORGANIK CAIR DARI AIR CUCIAN BERAS DI NAGARI LAWANG KECAMATAN MATUR KABUPATEN AGAM, SUMATERA BARAT - Efrizal Efrizal; Zozy Aneloi Noli; Solfiyeni Solfiyeni; Ferry Lismanto Syaiful; Amelia Sriwahyuni Lubis; Liza Febriani Sukma; Rahma Devi; M. Teguh Dhiya Ulhaq (LPPM Universitas Andalas, 2024)
The utilization of rice washing water waste from households has not been optimized, even though it contains a large amount of essential nutrients for plant growth. This waste can be utilized as natural fertilizer for horticultural plants. Rice washing water provides various benefits for plants, is easily accessible to farmers, and is also environmentally friendly. Additionally, its price is very affordable so it can be accessed by farmers. The purpose of this activity is to increase knowledge and understanding of the community in making Liquid Organic Fertilizer (LOF) derived from rice washing water waste, as well as to reduce the use of chemical fertilizers by shifting to organic fertilizers to maintain soil and environmental quality. This activity was conducted in Nagari Lawang, Matur District, Agam, West Sumatra. The method used was through lectures and demonstrations of liquid organic fertilizer (LOF) production. The results of this activity showed that the interaction between the organizers and participants had a positive impact, improving skills, and motivating PKK mothers in plant cultivation. The home garden is seen as a productive land for nutrition and income, but there are obstacles such as lack of knowledge and capital. Overcoming these obstacles requires increasing technical knowledge and providing capital. Furthermore, this activity also resulted in increased knowledge and active participation in the process of making liquid organic fertilizer. The conclusion of this activity is to increase knowledge and skills in making LOF, motivating intensive plant cultivation. Public interest in making LOF from waste is high, increasing knowledge and skills in producing organic fertilizer for successful plant cultivation.